Case report: Recurrence of inflammatory cardiomyopathy detected by magnetocardiography - Suwalski, Phillip; Golpour, Ainoosh; Musigk, Nicolas; Wilke, Finn; Landmesser, Ulf; Heidecker, Bettina (Frontiers in Cardiovascular Medicine, 2023)
Background: The diagnosis of inflammatory cardiomyopathies remains challenging. Life-threatening conditions such as acute coronary syndrome (ACS) always have to be considered as differential diagnoses due to similarities in presentation. Diagnostic methods for inflammatory cardiomyopathy include endomyocardial biopsy (EMB), cardiac magnetic resonance imaging (CMR), and positron emission tomography-computed tomography (PET-CT). We report a case, in whom magnetocardiography (MCG) led to the initial diagnosis of inflammatory cardiomyopathy and in whom MCG was used for subsequent monitoring of treatment response under immunosuppression. Case presentation: A 53-year-old man presented with 2 recurrent episodes of inflammatory cardiomyopathy within a 2-year period. The patient initially presented with reduced exercise capacity. Echocardiography revealed a moderately reduced left ventricular ejection fraction (LVEF 40%). Coronary angiography ruled out obstructive coronary artery disease (CAD) and an EMB was performed. The EMB revealed inflammatory cardiomyopathy without viral pathogens or replication. Also, we performed MCG, which confirmed a pathological Tbeg-Tmax vector of 0.108. We recently established a cutoff value of Tbeg-Tmax of 0.051 or greater for the diagnosis of inflammatory cardiomyopathy (1). Immunosuppressive therapy with prednisolone was initiated, resulting in clinical improvement and LVEF increase from 40% to 45% within one month. Also, the MCG vector improved to 0.036, which is considered normal based on our previous findings (1). The patient remained clinically stable for 23 months. During a routine follow-up, MCG revealed an abnormal Tbeg-Tmax vector of 0.069. The patient underwent additional testing including routine laboratory values, echocardiography (LVEF 35%), and PET-CT. PET-CT revealed increased metabolism in the myocardium – primarily in the lateral wall. Therapy with prednisolone and azathioprine was initiated and MCG was used to monitor the effect of immunosuppressive therapy. Conclusion: In addition to diagnostic screening, MCG has the potential to become a valuable method for surveillance monitoring of patients who have completed treatment for inflammatory cardiomyopathy. Furthermore, it could be used for treatment monitoring. While changes in the magnetic vector of the heart are not specific to inflammatory cardiomyopathy, as they may also occur in other types of cardiomyopathy, the MCG offers a tool of broad and efficient diagnostic screening for cardiac pathologies without side effects.